Pathways to sustainable land-use and food systems: 2019 Report of the FABLE Consortium - FABLE Consortium; DeClerck, Fabrice A.J.; Jones, S. (International Institute for Applied Systems Analysis (IIASA) and the Sustainable Development Solutions Network (SDSN), 2019)
This first report by the FABLE Consortium presents preliminary pathways towards sustainable land-use and food systems prepared by the 18 country teams from developed and developing countries, including the European Union. The aim of these pathways is to determine and demonstrate the technical feasibility of making land-use and food systems sustainable in each country. They can also inform mid-century low-emission development strategies under the Paris Agreement on Climate Change. FABLE country teams have aimed for consistency with the SDGs and the Paris Agreement objectives. At this early stage, not all target dimensions have been considered. The report does not discuss policy options for transforming these systems, their implementation, or associated costs and economic benefits. These critical issues will be addressed in the global report by the Food and Land-Use Coalition, which will be published in September 2019 ahead of the Climate Summit convened by UN Secretary-General António Guterres.